Answer:
146
Step-by-step explanation:
arrange your values in descending order then cancel out last value with the first value.
the middle value would be your answer.
hope it was helpfull.please give me a thanks
A function is said to even if it returns the same output when given two opposite inputs:
![f(x) = f(-x)](https://tex.z-dn.net/?f=%20f%28x%29%20%3D%20f%28-x%29%20)
In your case, you have
![f(x) = 1-\cos(x), \quad f(-x) = 1-\cos(-x)](https://tex.z-dn.net/?f=%20f%28x%29%20%3D%201-%5Ccos%28x%29%2C%20%5Cquad%20f%28-x%29%20%3D%201-%5Ccos%28-x%29%20)
And since
, the proof is concluded.
4 and 19/20 Yw brainly pleas
Answer:
Answer is in picture
Step-by-step explanation:
Hope it is helpful....